Entry and Transcription as Key Determinants of Differences in CD4 T-Cell Permissiveness to Human Immunodeficiency Virus Type 1 Infection - Ciuffi, Angela (American Society for Microbiology, 2004)
Isolated primary human cells from different donors vary in their permissiveness—the ability of cells to be infected and sustain the replication of human immunodeficiency virus type 1 (HIV-1). We used replicating HIV-1 and single-cycle lentivirus vectors in a population approach to identify polymorphic steps during viral replication. We found that phytohemagglutinin-stimulated CD4(+) CD45RO(+) CD57(−) T cells from healthy blood donors (n = 128) exhibited a 5.2-log-unit range in virus production. For 20 selected donors representing the spectrum of CD4 T-cell permissiveness, we could attribute up to 42% of the total variance in virus production to entry factors and 48% to postentry steps. Efficacy at key intracellular steps of the replicative cycle (reverse transcription, integration, transcription and splicing, translation, and budding and release) varied from 0.71 to 1.45 log units among donors. However, interindividual differences in transcription efficiency alone accounted for 64 to 83% of the total variance in virus production that was attributable to postentry factors. While vesicular stomatitis virus G protein-mediated fusion was more efficacious than CCR5/CD4 entry, the latter resulted in greater transcriptional activity per proviral copy. The phenotype of provirus transcription was stable over time, indicating that it represents a genetic trait.